Strategic Marketing planning in small/ Family owned business with reference to the Indian markets - Goyal, Vineet (2012)
This research is aimed at understanding the way in which the small family owned businesses manage their strategic management activities in their businesses. This research has been conducted with reference to the Indian businesses environment, as this is one nation wherein we see lot of family owned businesses even today. This paper is not just limited to any particular sector or industry but a combination of several industries in order to develop a generic view over the same. At the same time this also helps in understanding how things work in these different industries in a different manner. The main focus in here is to gain primary knowledge and for the same interviews was conducted with 10 respondents from various businesses. The research in here is a qualitative one with bits and pieces of quantitative research with an exploratory style of research.